A De Novo case of autosomal dominant mitochondrial membrane protein‐associated neurodegeneration. Issue 7 (27th May 2021) - Fraser, Stuart; Koenig, Mary; Farach, Laura; Mancias, Pedro; Mowrey, Kate
Abstract: Background: Mitochondrial membrane protein‐associated neurodegeneration (MPAN) is a genetic neurodegenerative condition previously thought to be inherited only in an autosomal recessive pattern through biallelic pathogenic variants in C19orf12 . Recent evidence has proposed that MPAN can also follow autosomal dominant forms of inheritance. We present a case of a de novo pathogenic variant in C19orf12 identified in a female with clinical features consistent with a diagnosis of MPAN, adding further evidence that the disease can be inherited in an autosomal dominant fashion. Methods: A 17‐year‐old Hispanic female was born to non‐consanguineous healthy parents. She developed progressive muscle weakness and dystonia beginning when she was 12 years old. Trio, whole‐exome sequencing with mitochondrial genome sequencing, and deletion/duplication analysis of both nuclear and mitochondrial genomes was performed in December 2019. Results: Whole‐exome sequencing analysis revealed a single de novo variant in C19orf12 . The specific variant is c.256C>T (p.Q86X) located in exon 3. Conclusion: Our clinical report provides further clinical evidence that MPAN can be inherited in an autosomal dominant or recessive fashion. The patient's age of onset and clinical symptoms are very similar to the previous patient published with this specific variant as well as others with heterozygous pathogenic variants in C19orf12 in Gregory et al. 2019. Our case report highlights the importance of considering both autosomal dominant and autosomal recessive version of MPAN with all patients demonstrating clinical features suggestive of MPAN. Abstract : This article presents a case of a patient with a heterozygous mutation in C19orf12. This gene causes Mitochondrial Membrane Protein Associated Neurodegeneration (MPAN), and has previously been thought to be caused only by autosomal recessive modes of inheritance. We reference two similar publications identifying heterozygous cases of MPAN, and emphasize that our clinical report provides further evidence that MPAN can be caused by homozygous or heterozygous genetic changes in C19orf12.